Influence of Material and Geometry on the Performance of Superconducting Nanowire Single-Photon Detectors - Henrich, Dagmar (Karlsruher Schriftenreihe zur Supraleitung / Hrsg. Prof. Dr.-Ing. M. Noe, Prof. Dr. rer. nat. M. Siegel, 2013)
Superconducting Nanowire Single-Photon Detectors offer the capability to detect electromagnetic waves on a single photon level in a wavelength range that far exceeds that of alternative detector types. However, above a certain threshold wavelength, the efficiency of those detectors decreases stronlgy, leading to a poor performance in the far-infrared range. Influences on this threshold are studied and approaches for improvement are verified experimentally by measurement of the device performance.